X-ray spectroscopic and scattering methods applied to the characterisation of cobalt-based Fischer–Tropsch synthesis catalysts. Issue 15 (29th June 2016) - Herbert, Jennifer J.; Senecal, Pierre; Martin, David J.; Bras, Wim; Beaumont, Simon K.; Beale, Andrew M.
Abstract : This review aims to critically assess the use of X-ray techniques, both of a scattering ( e.g. X-ray diffraction (XRD), pair distribution function (PDF)) and spectroscopic nature (X-ray absorption spectroscopy (XAFS)), in the study of cobalt-based Fisher–Tropsch synthesis (FTS) catalysts. Abstract : This review aims to critically assess the use of X-ray techniques, both of a scattering ( e.g. X-ray diffraction (XRD), pair distribution function (PDF)) and spectroscopic nature (X-ray absorption spectroscopy (XAFS)), in the study of cobalt-based Fisher–Tropsch Synthesis (FTS) catalysts. In particular, the review will focus on how these techniques have been successfully used to describe the salient characteristics of these catalysts that govern subsequent activity and selectivity, as well as to afford insight into deactivation phenomena that have seemingly stifled their application. We discuss how these X-ray-based techniques have been used to yield insight into the bulk structure, the catalyst surface, oxidation states, local (cobalt) geometry, and elemental composition of particles, primarily from a 1D perspective but we also highlight how, with recent developments in advanced X-ray characterisation methods, crucial information can now be obtained in 2D and 3D. The examples chosen focus on data acquired in situ / operando, under realistic operating conditions and during activation which often allow for obtaining a more relevant perspective on the changes in catalyst structure that accompany a change in catalyst performance. We conclude with a perspective on some of the challenges that beset the Co-based FTS technology and discuss how X-ray based techniques could be used to solve them.